KEDUDUKAN HUKUM DAN HAK ADVOKAT DALAM MEMBERIKAN BANTUAN HUKUM CUMA-CUMA PERKARA PIDANA DI TINJAU DARI UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Semuel Walangitan (Universitas Pamulang, 2016)
Indonesia as a state law (state of law) adheres to the idea of equality before the law (equality before the law) to ensure that each person gets treatment and legal certainty are equal in their rights and obligations as subjects of law regardless of social status. In fact, the economic factor is often a differentiator for justice seekers and cause social jealousy. Based on Pancasila as the nation and the fundamental mandate of the 1945 state guarantees the right of every seeker of justice to obtain assurance hukum.Bagi people can not be provided legal aid program which is regulated in Law No. 16 Year 2016 on Legal Aid. Advocates have a strategic position and juridical rights in providing legal assistance for free of charge are regulated by law. As a legal Counsel, Advocate is obliged to comply with the provisions of article 22 of Law Number 18 Year 2003 concerning Advocates which requires Advocates to provide legal assistance for free of charge to the justice seekers who tidakk capable.Keywords: legal status, rights advocates, criminal case